Trends in the population of Lviv region in the XIX-XXI centuries - Hudzelyak, Iryna; Perkhach, Oksana (Human Geography Journal, 2021)
The peculiarities of the population dynamics of the Lviv region from 1857 to the present are characterized. A brief overview of scientific works of Ukrainian and foreign geographers and other scientists on this issue, which have been published in recent years. The statistical materials for this study were the censuses of the Austrian Empire of 1857, the Austro-Hungarian Empire of 1869, 1880, 1890, 1900, 1910, the Polish censuses of 1921 and 1931, the Soviet censuses of 1859, 1970, 1979, 1989 and the All-Ukrainian census. 2001. The main method of research is historical and geographical. With its help the analysis of the population in modern borders of the Lviv area since the beginning of 1857 is carried out.In changes of the population of the Lviv area it is possible to allocate two stages: long growth before 1993 and the subsequent depopulation after 1993. The basis for the separation of these stages of the seven periods of population change. During the first period (1857-1910) the population of the region increased, for example in 1869 by 102 thousand people compared to 1857. In 1869-1880 the average annual growth rate was more than 2%. The second period (1910-1921) is marked by depopulation processes. This is due to significant demographic losses in the First World War and the national liberation war of the Ukrainian people. The third period (1921-1939) is characterized by population growth. The region was marked by a fairly high growth, as it did not suffer losses due to the Holodomor in Ukraine in 1932-1933. In the fourth period (1939-1946) the highest rates of depopulation were observed, due to the Second World War 1939-1945. at over 4%. In the fifth period (1946-1993) there was an increase in the population of the region. The number of urban population grew rapidly. At that time, as early as 1950, the population began to decline in rural areas. In the sixth period (1994-2009) the highest rates of depopulation are observed. Almost 80% of the total population decline in this period in the region was due to a negative migration balance. Lviv region in the seventh period (2010-2021) shows more favorable demographic trends compared to national ones. The rate of depopulation is slowing down: in 2013-2017, the population of the region decreased by only 0.08% annually, while in Ukraine - by 1.7%. As a result, the main reason for the decrease in the population of the region is the significant migration losses over several decades of the XX-XXI centuries.